Gas signatures from Escherichia coli and Escherichia coli‐inoculated human whole blood. Issue 1 (10th July 2013) - Umber, Brandon J; Shin, Hye‐Won; Meinardi, Simone; Leu, Szu‐Yun; Zaldivar, Frank; Cooper, Dan M; Blake, Donald R
Abstract: Background: The gaseous headspace above naïve Escherichia Coli ( E. coli ) cultures and whole human blood inoculated with E. coli were collected and analyzed for the presence of trace gases that may have the potential to be used as novel, non‐invasive markers of infectious disease. Methods: The naïve E. coli culture, LB broth, and human whole blood or E. coli inoculated whole blood were incubated in hermetically sealable glass bioreactors at 37°C for 24 hrs. LB broth and whole human blood were used as controls for background volatile organic compounds (VOCs). The headspace gases were collected after incubation and analyzed using a gas chromatographic system with multiple column/detector combinations. Results: Six VOCs were observed to be produced by E. coli ‐infected whole blood while there existed nearly zero to relatively negligible amounts of these gases in the whole blood alone, LB broth, or E. coli‐ inoculated LB broth. These VOCs included dimethyl sulfide (DMS), carbon disulfide (CS2 ), ethanol, acetaldehyde, methyl butanoate, and an unidentified gas S. In contrast, there were several VOCs significantly elevated in the headspace above the E. coli in LB broth, but not present in the E. coli /blood mixture. These VOCs included dimethyl disulfide (DMDS), dimethyl trisulfide (DMTS), methyl propanoate, 1‐propanol, methylcyclohexane, and unidentified gases R2 and Q. Conclusions: This study demonstrates 1) that cultivated E. coli in LB broth produce distinct gas profiles, 2) for the first time, the ability to modify E. coli ‐specific gas profiles by the addition of whole human blood, and 3) that E. coli ‐human whole blood interactions present different gas emission profiles that have the potential to be used as non‐invasive volatile biomarkers of E. coli infection.